A Different Pitch: Listening to Water Through Contemporary Art in a Time of Extraction - Beer, Ruth; Chaisson, Caitlin (Imaginations)

(untitled) (York University, 2019)
This article addresses the intersections of water, extraction, and environmental justice through a consideration of sound in contemporary artworks by Ruth Beer, Rebecca Belmore, and Mia Feuer. Qualities of sound have been tied to environmental studies and assessment for decades, but these artists consider audio-visual and immersive situations that foster the ability to listen amidst ecological complexity.